Acceptance of Moodle by professors: a study in a Portuguese Higher Education Institution - Costa, Carolina (2017)
This paper presents and discusses the results of a study carried out with professors of the University of Aveiro, Portugal (UA), which aim is to characterize their acceptance of Moodle. The data were collected through the application of a questionnaire based on the Technology Acceptance Model. In general, the professors expressed a positive attitude towards the items that measure the Perceived Ease of Use, the Perceived Usefulness, the Attitude Toward Using and the Social Influence. There were defined groups of professors based on gender, scientific area and age group, and statistical tests were performed. Although the majority of the items did not show any statistical significant differences between the groups, probably revealing that the use of Moodle is already widespread in the teaching and learning process at UA, it was possible to identify some differences, mainly with respect to gender and scientific area.